THE EFFECT OF GREEN ACCOUNTING, THIN CAPITALIZATION, AND SUSTAINABILITY REPORTING ON FINANCIAL STATEMENT TRANSPARENCY WITH PROFITABILITY AS A MODERATING VARIABLE - Chaerul Anam; Eko Sudarmanto (ZILLZELL MEDIA PRIMA, 2026)
The purpose of this study is to examine the effects of green accounting, thin capitalization, and sustainability reporting on financial reporting transparency, and to determine the moderating role of profitability in these relationships. This research uses a quantitative approach with an explanatory design based on panel data from industrial sector companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2024. Data were analyzed using EViews 12 with panel regression to test six hypotheses. The results show that green accounting has a positive and significant effect on financial reporting transparency, while thin capitalization has no significant effect. In contrast, sustainability reporting has a negative and significant effect on transparency. Profitability is found to weaken the relationship between green accounting and financial transparency but strengthen the relationship between sustainability reporting and financial transparency. These findings highlight the importance of integrating environmental accounting and responsible disclosure practices to enhance the credibility, accountability, and transparency of corporate financial reports in Indonesia’s industrial sector.